Project Bin&Go : a public relations campaign to promote fuss-free recycling with Sentosa. - Mohamed Fadzil Mohamed Hisum. (2013)
This paper presents the collaboration between four students of Nanyang Technological University Wee Kim Wee School of Communication and Information and Sentosa’s Corporate Planning Division to promote an environmental initiative to the patrons of Sentosa, in Singapore. Working in line with Sentosa’s Green Plan as part of their Corporate Social Responsibility Programme, Project Bin&Go is a campaign which aims to promote fuss-free recycling and increase recycling efforts by guests and staff on Sentosa. This was done through various guest and staff engagement events to educate them on recycling, as well as implementing long-term initiatives such as increasing the number of recycling outlets on the island. The report provides an insight into the campaign’s development, from idea conception to execution and final evaluation. The findings from the campaign are also evaluated for future directions, addressing possible implications on increased number of recycling outlets as well as feasibility of extending campaign efforts beyond Sentosa’s shores.